Design and Implementation of the Mission Planning Functions for the KOMPSAT-2 Mission Control Element - Byoung-Sun Lee; Jae-Hoon Kim (Journal of Astronomy and Space Sciences, 2003)
Spacecraft mission planning functions including event prediction, mission scheduling, command planning, and ground track display have been developed for the KOMPSAT-2 mission operations. Integrated event prediction functions including satellite orbital events, user requested imaging events, and satellite operational events have been implemented. Mission scheduling functions have been realized to detect the mission conflicts considering the user specified constraints and resources. A conflict free mission scheduling result is mapped into the spacecraft command sequences in the command planning functions. The command sequences are directly linked to the spacecraft operations using eXtensible Markup Language (XML) for command transmission. Ground track display shows the satellite ground trace and mission activities on a digitized world map with zoom capability.